2000
DOI: 10.1107/s0021889899013229
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the behaviour of polymers in supercritical fluids and organic solvents via small-angle neutron scattering

Abstract: Small-angle neutron scattering has been used to study the effect of temperature and pressure on the phase behaviour of semidilute solutions of polymers dissolved in organic and supercritical solvents. Above the theta temperature (T Θ ), these systems exhibit a "good solvent" domain, where the molecules expand beyond the unperturbed dimensions in both organic solvents and in CO 2 . However, this transition can be made to occur at a critical "theta pressure" (P Θ ) in CO 2 and this represents a new concept in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…In addition to lowering the UCSD and the theta density for the homopolymer in bulk CO 2 , increasing the temperature has been found to have a pronounced effect on the solvation of stabilizing tails in CO 2 , as observed both theoretically [32,64] and experimentally [38,63]. On the basis of Monte Carlo simulations, Luna-Barcenas and coworkers [32] reported that the mean square end-to-end distance of a Lennard-Jones polymer chain in an L-J solvent increased monotonically as the temperature was increased at constant density.…”
Section: Effect Of Temperature On Cfdmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition to lowering the UCSD and the theta density for the homopolymer in bulk CO 2 , increasing the temperature has been found to have a pronounced effect on the solvation of stabilizing tails in CO 2 , as observed both theoretically [32,64] and experimentally [38,63]. On the basis of Monte Carlo simulations, Luna-Barcenas and coworkers [32] reported that the mean square end-to-end distance of a Lennard-Jones polymer chain in an L-J solvent increased monotonically as the temperature was increased at constant density.…”
Section: Effect Of Temperature On Cfdmentioning
confidence: 89%
“…Yet another factor for the observed decrease in the CFD at elevated temperatures is the weakening of the dipole-dipole interactions between the PFOMA tails as temperature is increased. Temperature has been shown to have a pronounced effect on the phase behavior for both PFOA [29,56] and PDMS [31,63] homopolymers. These studies indicated a decrease in both the UCSD and the theta density as the temperature was increased, and the same trend was observed for the PFOMA homopolymer in this study (Fig.…”
Section: Effect Of Temperature On Cfdmentioning
confidence: 98%
See 1 more Smart Citation
“…This behavior has been investigated by optical microscopy [14], turbidimetry [78][79][80], SANS [81,82], and Monte Carlo simulations [83]. When the density is held constant, the C-W c o decreases slightly as the temperature is elevated up to 70°C.…”
Section: Effect Of Temperaturementioning
confidence: 98%
“…The study of conformational properties (i.e., hydrodynamic radius) of polymers in supercritical fluids has been an area of active research. Some commonly used supercritical fluids (ScF) for polymers include carbon dioxide (CO 2 ),1–4 ethane (C2),1, 3, 5, 6 and propane (C3)1, 3, 5, 7–9 due to their relatively low‐critical temperatures and pressures. The solubility of polystyrene (PS) in these three supercritical fluids is well known 1, 5, 10.…”
Section: Introductionmentioning
confidence: 99%